Mathematical modelling of uncertainty in a process of provisioning at a comercial enterprise - Anna M. Gil-Lafuente; Anna Klimova (The International Journal of Management Science and Information Technology (IJMSIT), 2014)
The survival of a business is nowadays more than ever a matter of utmost importance. The process of globalization and current economic crisis are the two main reasons that caused the situation of uncertainty and instability on the world market. In this paper we made a theoretical approach and practical development of the study case related with the food inventory process at a small or medium-sized enterprises commercial enterprise. We used a mathematical tool based on one of the well-known classical methods that consists of calculating an inventory/supply rate with the transition into uncertain environment using some elements of fuzzy arithmetic. This model is sensible to many economical factors and gives a level of inventory stock that is optimal for the company at each moment.
Keywords: 650; Globalization; Economic Crisis; Logistics; Supply Chain; Fuzzy Mathematics